Advancing sustainable mobility in India with electric vehicles: market trends and machine learning insights - Ezhilmaran Devarasan; Deepikaa Nagarajan; Jenisha Rachel (Frontiers in Energy Research)
India, as a rapidly growing country facing significant pollution challenges, sees a major opportunity for sustainable mobility through the adoption of electric vehicles. Since a large amount of India’s crude oil is imported, the country is vulnerable to changes in the price of crude oil globally. India may improve its energy security and lessen its reliance on imported fossil fuels by switching to electric vehicles (EVs) that are powered by electricity generated domestically. Air pollution from internal combustion engine vehicles is a contributing factor to several health issues, such as heart disease and respiratory disorders. Making the switch to EVs can result in better public health outcomes and cleaner air. This study offers an in-depth analysis of India’s Electric Vehicle (EV) market dynamics from FY 2014 to February 2024, utilizing machine learning techniques to identify sales trends, regional disparities, and adoption drivers. Through meticulous examination, the research aims to elucidate sales trends, regional variations, and underlying factors influencing EV adoption across the nation. Objectives include analysing sales trajectories over the past decade, estimating EV sales across states, exploring category-specific trends, identifying drivers of regional disparities, investigating EV adoption patterns in the Tamil Nadu, evaluating the advantages and disadvantages of EVs. With a particular interest in analyzing the complex dynamics of charging infrastructure in cities, this study extensively examines EV adoption in India. By using data-driven insights, this research aims to contribute to a deeper understanding of the dynamics shaping the EV landscape in India and provide valuable guidance for stakeholders, industry participants and policymakers on how to promote the country’s electric mobility sector’s sustainable growth.